Acculturation and Health-Promoting Lifestyle among Nigerian Americans - Frank Akpati; Jennifer Kawi (SAGE Open)
The health status of Nigerian Americans is poorly documented due to data aggregation with other Black ethnicities. This study examined acculturation, health status, and health-promoting lifestyle among Nigerian Americans. This study was conducted remotely utilizing a cross-sectional, quantitative design, with path analyses (N = 161). Acculturation, guided by Berry’s model, was conceptualized through ethnic and dominant society immersion (Stephenson Multigroup Acculturation Scale). Health-promoting lifestyle was measured using Health-Promoting Lifestyle Profile-II and health status through SF-12. Both ethnic and dominant society immersion significantly predicted all health-promoting lifestyle domains; spiritual growth had the largest β coefficient (.35 and .30 respectively) and had a positive predictive effect on physical (β = .38) and mental health (β = .34). Further, interpersonal relations was positively associated with mental health (β = .30). Study findings can impact healthcare practices, particularly culturally congruent care, and policy influencing health outcomes and healthcare equity.